Conceptual Complexity and the Helping Relationship - Van Hesteren, Frank; Sawatsky, Donald D.; Zingle, Harvey W. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this article is to provide a perspective on the relevance of conceptua lcomplexity theory to counselling. Some origins of conceptual complexity theory are traced and descriptions of current theoretical positions are provided.Potential counselling applications of conceptual complexity are discussed and examples of research efforts bearing on such applications are given.